Retinal biomarkers predict future cognitive performance in progranulin‐haploinsufficient frontotemporal dementia. (December 2021) - Oertel, Frederike Cosima; Younes, Kyan; Cobigo, Yann; Keihani, Azeen; Fonseca, Corrina; Bennett, Daniel J; Abdelhak, Ahmed; Saias, Alexandra; Montes, Shivany Condor; Chen, Robert Y; Cordano, Christian; Green, Ari J; et al.
Abstract: Background: Progranulin (GRN) haploinsufficiency caused by heterozygous mutations in the GRN gene is a common cause of early‐onset familial frontotemporal dementia (FTD). Our group previously described neuronal ceroid lipofuscinosis‐like features in the retinae of asymptomatic and mildly symptomatic heterozygous GRN mutation carriers ( GRN ‐carriers). However, additional intraretinal changes, their clinical relevance and utility as biomarkers remain unexplored. We aimed to describe the distinct retinal disease pattern in GRN‐carriers and to investigate the association of retinal change with subsequent brain atrophy and cognitive decline. Method: We applied optical coherence tomography (OCT) and scanning laser ophthalmoscopy at baseline in 23 GRN‐carriers (age [years, mean+SD]: 62±11, gender [male, N(%)]: 11(48), mean Clinical Dementia Rating (CDR) = 0.5; CDR = 0.0 for 9 subjects) and 85 healthy controls (HCs) (age: 69±15, gender: 42(49)), investigating qualitative and quantitative retinal changes. Linear mixed‐effect models (LME) were used to study the relationships at a group‐level between OCT findings and longitudinal assessments (follow‐up time [months, median(min‐max)]: 28(12‐73)) of cognitive performance including lexical fluency (LF), semantic fluency (SF) and emotion naming (EN). MRI analyses are pending. Result: Eight eyes (17%) of five GRN‐carriers (22%) had drusen‐like depositions detectable on OCT. Quantifying macular layers, GRN‐carriers had a thicker outer plexiform layer (OPL: 0.33±0.05mm 3, p<0.001), thinner outer nuclear layer (ONL: 0.66±0.07mm 3, p = 0.019) and thinner retinal pigment epithelium (RPE: 0.15±0.02mm 3, p = 0.039) compared with HC (OPL: 0.30±0.03mm 3, ONL: 0.69±0.07mm 3, RPE: 0.16±0.01mm 3 ), but no differences in inner retinal layers (confirmed excluding eyes with drusen). The OPL/ONL‐ratio was higher in GRN‐carriers (0.51±0.13) than HC (OPL/ONL‐ratio: 0.44+0.08, B = 0.079, p<0.001). GRN‐carriers with OPL/ONL‐ratio>median at baseline had a faster annualized decline of LF (‐2.60±5.62, B = 0.273, p = 0.002), SF (‐5.70±9.76, B = 0.213, p = 0.035) and EN (0.44±1.24, B = 0.066, p = 0.040) during follow‐up compared to subjects with OPL/ONL‐ratio<median (LF: 4.25±3.50; SF: 0.00±4.32, EN: 2.00±1.83). Conclusion: GRN‐haploinsufficiency is associated with retinal phenotypes, including drusen and outer retinal layer thinning, suggestive of photoreceptor degeneration. OPL/ONL‐ratio predicted FTD associated cognitive worsening ‐ and thereby might have potential as biomarker of disease progression in clinical trials.